Moments and number of defoliated leaves and hybrid corn productivity - Ramirez, J.; Soto, A.; Durán, C. E.; Luis, D. B. (Peruvian Agricultural Research, 2019)
Abstract Objectives: To determine the effect of the time and the number of lower leaves defoliated, on the productivity of hybrid corn (Zea mays L.). Methodology: Randomized complete blocks design was used, with arrangement of split plot and four replications, using the hybrid cultivar DK 7088. The plots corresponded to the defoliation times: 0, 14 and 28 days after pollination (DAP) and the subplots, number of defoliated leaves (DL): zero, two, four and six. The leaves were defoliated just below the ear, from top to the bottom. The total number of treatments was 12. Scott-Knott statistical test with a level of 5 % was used for the comparison of means. The traits studied were grain weight per ear, ear weight and grain yield per hectare. Results: The interaction between defoliation time and number of lower defoliated leaves was significant (P < 0.05) for grain weight per ear, ear weight and grain yield. The defoliation of two, four and six leaves during pollination reduced the grain weight per ear, weight per cob and grain yield, being significantly lower than the no defoliated plants. At 14 and 28 days after pollination, defoliation did not affect significantly (P > 0.05) grain yield, but grain weight per ear and ear weight decreased (P < 0.05). Conclusions: The defoliation of lower leaves made during the pollination, reduces the grain weight per ear, ear weight and grain yield, while defoliation 14 days after pollination did not affect significantly the grain yield per hectare. Keywords: Zea mays, defoliation, leaves, grain yield